2015
DOI: 10.1007/978-1-4939-2782-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Clustering in Inhibitory Neural Networks with Nearest Neighbor Coupling

Abstract: We investigate the clustering dynamics of a network of inhibitory interneurons, where each neuron is connected to some set of its neighbors. We use phase model analysis to study the existence and stability of cluster solutions. In particular, we describe cluster solutions which exist for any type of oscillator, coupling and connectivity. We derive conditions for the stability of these solutions in the case where each neuron is coupled to its two nearest neighbors on each side. We apply our analysis to show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 25 publications
6
14
0
Order By: Relevance
“…He showed that these results gave a good prediction of stability for a variety of model networks. Recently, similar results have been obtained for networks with nearest-neighbour coupling [21]. Phase model analysis has been extensively used to study phase-locking in pairs of model and experimental neurons [12,22,19].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…He showed that these results gave a good prediction of stability for a variety of model networks. Recently, similar results have been obtained for networks with nearest-neighbour coupling [21]. Phase model analysis has been extensively used to study phase-locking in pairs of model and experimental neurons [12,22,19].…”
Section: Introductionsupporting
confidence: 64%
“…Theorem 6. For a network with a circulant connectivity matrix, the system (10) admits solutions of the form (20) and (21) if N = 4p for some integer p, and p−1 k=0 w 4k+1 = p−1 k=0 w 4k+3 .…”
Section: Other Types Of Cluster Solutionsmentioning
confidence: 99%
“…Thus we conclude that the 1-cluster (totally synchronized) solution always exists. This is consistent with results for systems with first and second nearest neighbour coupling [31]. To proceed further, take the difference of equations 22 Repeating this with other pairs of equations leads to the same constraint on ψ m and the conditions (21).…”
Section: The Second Case: K Th Neighbor Coupling With Additional Coupsupporting
confidence: 73%
“…In neural network models, the formation of neural assemblies has been analyzed by identifying cluster solutions in networks of intrinsically oscillating neurons [16,17,28,15,22,31,7]. Clustering defines a type of solution where the network of oscillators breaks into subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work [31,7], we used the phase model approach to determine existence and stability conditions of cluster solutions of networks with neurons arranged in a 1-dimensional ring, of arbitrary size, with various connectivity schemes. As in many other studies [5,33], our work focused on cluster solutions where the phase difference between any two adjacent neurons in the network is the same.…”
Section: Introductionmentioning
confidence: 99%